Comparative study on the quality of two rice (Oryza sativa) varieties produced under organic and conventional systems - Juanico, Sami Clarisse Tardaguela
Randomized Complete Block Design (RCBD) experiment was performed during the late wet season to compare the performance of two commercial rice varieties.